Combining Context-Awareness with Wearable Computing for Emotion-based Contents Service - Lee, Haesung; Kwon, Joonhee (International Journal of Advanced Science and Technology, 2010)
One important but often overlooked aspect of human contexts of ubiquitous computing environment is human’s emotional status. And, there are no realistic and robust humancentric contents services so far, because there are few considers about combining context awareness computing with wearable computing for improving suitability of contents to each user’s needs. In this paper, we discuss combining context awareness computing with wearable computing to develop more effective personalized services. And we propose new algorithms to develop efficiently personalized emotion based content service system.